Tradisi Manak Salah di Desa Adat Padangbulia Kecamatan Sukasada Kabupaten Buleleng - Ni Luh Gede Astari Dewi; I Ketut Sukadana; Diah Gayatri Sudibya (Jurnal Konstruksi Hukum, 2021)
Manak salah is a tradition carried out by the Padangbulia indigenous people who consider that the birth of tapered twins (male and female) is a mistake which obliges the parents and the tapered twins to undergo temporary isolation for three months. This was considered contrary to humanity so that the government issued Regional Regulation Number 10 of 1951 concerning the Elimination of Manak Salah or Buncing Customs. This study aims to explain the manak salah tradition in the traditional village of Padangbulia and what are the factors causing the implementation of the manak salah tradition in the traditional village of Padangbulia. The research used is empirical legal research with a sociology of law approach and a case approach by looking at real legal events that occurred in Padangbulia Village and the sources of legal materials used are primary and secondary legal materials with techniques of collecting legal materials through interviews and recording which are analyzed qualitatively in The descriptive form of the analysis shows that Manak was wrongly implemented in accordance with the beliefs of the Padangbulia people with the palm-leafed god tatwa and brahma sapa which were used as the basis for the implementation of this tradition since time immemorial. Even though the manak salah tradition has been abolished, it is still being carried out today because of the belief of the Padangbulia indigenous people about the disasters that will occur if this tradition is not implemented.